Utility of macrophages in an antitumor strategy based on the vectorization of iron oxide nanoparticles. Issue 19 (5th April 2019) - Dalzon, Bastien; Guidetti, Mélanie; Testemale, Denis; Reymond, Solveig; Proux, Olivier; Vollaire, Julien; Collin-Faure, Véronique; Testard, Isabelle; Fenel, Daphna; Schoehn, Guy; Arnaud, Josiane; Carrière, Marie; et al.
Abstract : Anticancer using Fe2 O3 -laden macrophages. Macrophages derived from patients are treated by Fe2 O3 nanoparticles and reinjected into the bloodstream. They are attracted by the tumor where they accumulate. Low-intensity radiation activates iron NPs, which release toxic photoelectrons in the tumor, leaving the surrounding tissue undamaged. Abstract : Many solid tumors and their metastases are still resistant to current cancer treatments such as chemo- and radiotherapy. The presence of a small population of Cancer Stem Cells in tumors is held responsible for relapses. Moreover, the various physical barriers of the organism ( e.g. blood–brain barrier) prevent many drugs from reaching the target cells. In order to alleviate this constraint, we suggest a Trojan horse strategy consisting of intravascular injection of macrophages loaded with therapeutic nanoparticles (an iron nanoparticle-based solution marketed under the name of FERINJECT®) to bring a high quantity of the latter to the tumor. The aim of this article is to assess the response of primary macrophages to FERINJECT® via functional assays in order to ensure that the macrophages loaded with these nanoparticles are still relevant for our strategy. Following this first step, we demonstrate that the loaded macrophages injected into the bloodstream are able to migrate to the tumor site using small-animal imaging. Finally, using synchrotron radiation, we validate an improvement of the radiotherapeutic effect when FERINJECT®-laden macrophages are deposited at the vicinity of cancer cells and irradiated.